Innovative shallow sump customizations for aero-engine bearing chambers - Chandra, Budi; Simmons, Kathy (2016)
Aero-engines incorporate various bearing chambers and these typically contain bearings, seals, rotating shafts, stationary walls and struts, and sometimes gears. Oil is supplied for lubrication and cooling and is removed (scavenged) from the sump region of the chamber (note that in some parts of the world the entire bearing chamber is referred to as the sump). Depending on the location and function of the bearing chamber, the sump region may be deep or shallow. Effective oil removal is essential as unnecessary working of the oil can lead to excessive heat generation and reduced overall efficiency. Therefore the design of the scavenge region in a bearing chamber, as well as the ability to assess its performance is very important.